2019
DOI: 10.1159/000496980
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Approach on Patient-Reported Outcomes after Radical Prostatectomy: A Propensity Score-Weighted Analysis from a Multicenter, Prospective, Observational Study (The Pros-IT CNR Study)

Abstract: Background: To report health-related quality of life outcomes as assessed by validated patient-reported outcome measures (PROMs) after radical prostatectomy (RP). ­Methods: This study analyzed patients treated with RP within The PROState cancer monitoring in Italy, from the National Research Council (Pros-IT CNR). Italian versions of Short-Form Heath Survey and university of California los Angeles-prostate cancer index questionnaires were administered. PROMs were physical composite scores, mental composite sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The Authors concluded that both RARP and ORP yielded similar functional outcomes at 24 months, but they advised using caution in interpreting the oncological outcomes [25]. Pros-IT CNR data also support this conclusion [26].…”
Section: Discussionmentioning
confidence: 99%
“…The Authors concluded that both RARP and ORP yielded similar functional outcomes at 24 months, but they advised using caution in interpreting the oncological outcomes [25]. Pros-IT CNR data also support this conclusion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Active surveillance retained the sexual function statistically significantly better than surgery, which led to the largest deterioration in sexual activity among the treatment lines. We did not assess differences of radical prostatectomy approaches (open, laparoscopic, and robot-assisted); however, another study found that there were significant differences in urinary and sexual dimensions, but their clinical significance seemed limited [20]. The treatment line turned out as a prognostic factor for survival and HRQoL also in our material as the choice of PC treatment is mainly based on T-classification and Gleason score, both known to be significant prognostic factors in PC.…”
Section: Discussionmentioning
confidence: 99%
“…The rising number of oncological surgical procedures delivered by robotic systems and the ongoing debate over their cost‐effectiveness led to an increased interest in the collection of patient reported measures from those who undergo this kind of surgical intervention. Most of the published studies present experiences of PROMs collection in clinical trials especially for patients who receive robotic radical prostatectomy , while no evidence has been found of systematic collection of patient reported measures for robotic oncological surgery.…”
Section: Discussionmentioning
confidence: 99%
“…PROMs data have been initially introduced in clinical trials in order to integrate the clinical data with the people's subjective perception of their health status and health‐related quality of life . Most studies present the results of clinical trials and focus on radical prostatectomy and use PROMs as a comparative tool between the outcomes achieved by cohort of patients operated by the open, laparoscopic or robotic technique , while in literature the evidence of systematic collection of patient reported measures is still limited. However, the intrinsic characteristic of oncological diseases where treatment is not a one‐shot event but a pathway that moves across the different care settings requires the design of performance measurement tools that are able to overcome the “silo‐vision” and evaluate performance results of the entire care pathway .…”
Section: Introductionmentioning
confidence: 99%